Low tidal volume ventilation ameliorates left ventricular dysfunction in mechanically ventilated rats following LPS-induced lung injury. Issue 1 (December 2015) - Cherpanath, Thomas; Smeding, Lonneke; Hirsch, Alexander; Lagrand, Wim; Schultz, Marcus; Groeneveld, AB
Abstract Background High tidal volume ventilation has shown to cause ventilator-induced lung injury (VILI), possibly contributing to concomitant extrapulmonary organ dysfunction. The present study examined whether left ventricular (LV) function is dependent on tidal volume size and whether this effect is augmented during lipopolysaccharide(LPS)-induced lung injury. Methods Twenty male Wistar rats were sedated, paralyzed and then randomized in four groups receiving mechanical ventilation with tidal volumes of 6 ml/kg or 19 ml/kg with or without intrapulmonary administration of LPS. A conductance catheter was placed in the left ventricle to generate pressure-volume loops, which were also obtained within a few seconds of vena cava occlusion to obtain relatively load-independent LV systolic and diastolic function parameters. The end-systolic elastance / effective arterial elastance (Ees/Ea) ratio was used as the primary parameter of LV systolic function with the end-diastolic elastance (Eed) as primary LV diastolic function. Results Ees/Ea decreased over time in rats receiving LPS (p = 0.045) and high tidal volume ventilation (p = 0.007), with a lower Ees/Ea in the rats with high tidal volume ventilation plus LPS compared to the other groups (p < 0.001). Eed increased over time in all groups except for the rats receiving low tidal volume ventilation without LPS (p = 0.223). A significant interaction (p < 0.001) was found between tidal ventilation and LPS for Ees/Ea and Eed, and all rats receiving high tidal volume ventilation plus LPS died before the end of the experiment. Conclusions Low tidal volume ventilation ameliorated LV systolic and diastolic dysfunction while preventing death following LPS-induced lung injury in mechanically ventilated rats. Our data advocates the use of low tidal volumes, not only to avoid VILI, but to avert ventilator-induced myocardial dysfunction as well.